Religious Concepts that generate difficulty in translation from Arabic into English - Hayif Sameer, Imad; Adnan Majeed, Wuud (Opción, 2019)
Translation from a language to a target language is a difficult task. This diffi- culty is manifested clearly in religious texts because they usually contain specific terms that do not have exact equivalence. In the past, it is normal to say ‘In the name of God’ but the specialists in religion say that the word ‘God’ must be replaced by ‘Allah’ because there is a huge difference between the two expressions. In this study, the researcher discusses the term culture and translation with the explanation of its types and problems focu- sing on cultural problem because it is core of this study. No one can translate from Arabic language into English in a good way without having an idea about the two cultures. The word ‘money’ is uncountable in English but in Arabic the opposite is true; therefore, it is accepted to say to someone who gave you a sum of money “I will count them and it” while this is unaccepted in English. Be familiar with the culture of the target language is the best way to write a good translation. The aim of this study is to clarify the role of culture in translation and the effect of it in changing the connotation meaning of specific religious words. The study hypothesizes that the conno- tation meaning of specific words differs from one culture into another. The results confirm this hypothesis. At the end of the study, there are conclusion and recommendations.